Enantiospecific effects of chiral drugs on cytochrome P450 inhibition in vitro. (2nd April 2016) - Krasulova, Kristyna; Siller, Michal; Holas, Ondrej; Dvorak, Zdenek; Anzenbacher, Pavel
Abstract: 1. The aim of this work was to examine the differences in the inhibitory potency of individual enantiomers and racemic mixtures of selected chiral drugs on human liver microsomal cytochromes P450. 2. The interaction of enantiomeric forms of six drugs (tamsulosin, tolterodine, citalopram, modafinil, zopiclone, ketoconazole) with nine cytochromes P450 (CYP3A4, CYP2E1, CYP2D6, CYP2C19, CYP2C9, CYP2C8, CYP2B6, CYP2A6, CYP1A2) was examined. HPLC methods were used to estimate the extent of the inhibition of specific activity in vitro . 3. Tamsulosin (TAM) and tolterodine (TOL) inhibited CYP3A4 activity with an enantiospecific pattern. The inhibition of CYP3A4 activity differed for R-TAM ( Ki 2.88 ± 0.12 µM) and S-TAM ( Ki 14.22 ± 0.53 µM) as well as for S-TOL ( Ki 1.71 ± 0.03 µM) and R-TOL ( Ki 4.78 ± 0.17 µM). Also, the inhibition of CYP2C19 by ketoconazole (KET) cis -enantiomers exhibited enantioselective behavior: the (+)-KET (IC50 23.64 ± 6.25 µM) was more potent than (−)-KET (IC50 66.12 ± 12.6 µM). The inhibition of CYP2C19 by modafinil (MOD) enantiomers (R-MOD IC50 = 51.79 ± 8.58 µM, S-MOD IC50 = 48.62 ± 9.74 µM) and the inhibition of CYP2D6 by citalopram (CIT) enantiomers (R-CIT IC50 = 68.17 ± 5.70 µM, S-CIT IC50 = 62.63 ± 7.89 µM) was not enantiospecific. 4. Although enantiospecific interactions were found (TAM, TOL, KET), they are probably not clinically relevant as the plasma levels are generally lower than the drug concentration needed for prominent inhibition (at least 50% of CYP activity).